Fetal vascular malperfusion, an update. Issue 7 (24th July 2018) - Redline, Raymond W.; Ravishankar, Sanjita
Abstract : Fetal vascular malperfusion is the most recent term applied to a group of placental lesions indicating reduced or absent perfusion of the villous parenchyma by the fetus. The most common etiology of malperfusion is umbilical cord obstruction leading to stasis, ischemia, and in some cases thrombosis. Other contributing factors may include maternal diabetes, fetal cardiac insufficiency or hyperviscosity, and inherited or acquired thrombophilias. Severe or high grade fetal vascular malperfusion is an important risk factor for adverse pregnancy outcomes including fetal growth restriction, fetal CNS injury, and stillbirth. Overall recurrence risk for subsequent pregnancies is low.